2011
DOI: 10.1089/jpm.2010.0281
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Clinical Rotation in Hospice: Medical Students' Perspectives

Abstract: Medical educators agree that training in end-of-life care (EOLC) must be an integral part of medical education at all levels. While progress in this area of education has taken place, many gaps still exist. This article describes the self-reported impact of a required one-week hospice rotation for third-year medical students. Students completing their hospice rotation during a one-year period were asked to write an essay describing the most important lessons they learned. Qualitative analyses of the essays rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…38 The literature supports this trend with examples of recently implemented medical student PC curricula incorporating reflective essays. [39][40][41][42][43] These publications highlight the powerful impressions and important lessons students wrote about, 39,40 and report student themes focused on what was learned, including about themselves, the patient, and being a doctor, and what was experienced, including internal emotional responses and self-transformation. 41 These authors however, did not use the specific lens of professionalism to analyze their essay data.…”
Section: Discussionmentioning
confidence: 99%
“…38 The literature supports this trend with examples of recently implemented medical student PC curricula incorporating reflective essays. [39][40][41][42][43] These publications highlight the powerful impressions and important lessons students wrote about, 39,40 and report student themes focused on what was learned, including about themselves, the patient, and being a doctor, and what was experienced, including internal emotional responses and self-transformation. 41 These authors however, did not use the specific lens of professionalism to analyze their essay data.…”
Section: Discussionmentioning
confidence: 99%
“…5 Many training initiatives have been implemented at different points throughout undergraduate medical training. [6][7][8][9][10][11][12][13] These have included 20-hour mandatory coursework sessions 7 ; 1-day visits to a hospice 8 ; 16 hours in a community hospice 9 ; a 4-day curriculum 6,10 ; and 1 week, 2 weeks, or 3 weeks of palliative care attachments (i.e., clinical electives) during the clinical years. [11][12][13] However, there is little information available to guide medical educators in how to best incorporate the teaching of palliative care into medical curricula.…”
mentioning
confidence: 99%
“…6,7,11 Studies report that students learn about the value of hospice care, the value of empathy, the value of the doctor-patient relationship, 12 and what it means to be a doctor 13 ; acknowledge a difference between resignation and acceptance; and start to understand death as a natural event. 8 Furthermore, students describe feeling more support and having a richer experience of role modeling after training in palliative care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As others have observed from similar studies, students were aware of the value of hospice and palliative care, identified the role of palliative care team members and understood death as a natural event through learning experiences in palliative care and hospice settings. 12,13 14 Unlike other studies with students in one discipline [12][13][14][15] , this study could be useful in understanding the dynamics of incorporating teamwork concepts within an interdisciplinary educational experience. In addition, other studies did not consider student suffering that could result from this type of clinical observation experience.…”
Section: Discussionmentioning
confidence: 99%